Analisis pertumbuhan bank syariah pasca pandemi - Umam, Reza Khoirul (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the growth of sharia banking in Indonesia after the Covid-19 pandemic. The pandemic that started at the end of 2019 has had a significant impact on various economic sectors, including the banking sector. Islamic banks in Indonesia face challenges in lending, declining asset quality and net interest margins. This study highlights the credit restructuring policy by the OJK and lowering interest rates by Bank Indonesia as steps to mitigate the economic impact. The research results show that despite the global economic downturn, sharia banking in Indonesia has succeeded in showing positive performance with significant growth in assets and Third Party Funds (DPK). This article is important for academics and practitioners to understand the dynamics of post-pandemic Islamic banking and the strategies implemented to overcome these challenges.